Development of the Healthy Pathways Child-Report Scales - Bevans, Katherine B. (Springer Netherlands, 2010)
PURPOSE: The Child Health and Illness Profile (CHIP) has separate child (6–11 years) and adolescent (12–21 years) editions that measure youth’s self-assessed health, illness, and well-being. The purpose of this study was to revise the CHIP by combining the two editions to create the Healthy Pathways Child-Report Scales. METHODS: We modified the original CHIP domains of Comfort, Risk Avoidance, Satisfaction, and Resilience to reflect advances in child health conceptualization. Classical test and item response theory psychometric analyses were conducted using data collected from 2,095 children (49% boys, 80% White, 17% African-American, 3% Hispanic, Age: M = 10.6, SD = 1.0) in grades 4–6 at 34 schools. RESULTS: After minor revisions, 16 of the 17 scales were found to measure unidimensional self-assessed health, illness, and well-being constructs comprehensively, but with a minimal number of items. Scales were unbiased by age, gender, survey modality, and geographic location. Construct validity was demonstrated by the instrument’s capacity to differentiate among children with and without chronic illnesses and to detect expected age and gender differences. CONCLUSIONS: The Healthy Pathways Child-Report Scales may be used to reliably and accurately assess unidimensional aspects of health, illness, and well-being in clinical and population-based research studies involving youth in transition from childhood to adolescence.